2013
DOI: 10.1007/s10329-013-0345-7
|View full text |Cite
|
Sign up to set email alerts
|

Ranging and foraging of Himalayan grey langurs (Semnopithecus ajax) in Machiara National Park, Pakistan

Abstract: Grey langurs (Semnopithecus spp.) occupy a variety of habitats, ranging from lowland forests and semi-desert to alpine forests. Little is known about their foraging and ranging in alpine forests, which appear to contain less food than lowland forests. We conducted a 1-year study of Himalayan grey langurs (Semnopithecus ajax) in Machiara National Park, Pakistan, where they occur at relatively high altitudes (range 2000-4733 m). We followed three groups of different sizes and compositions and examined the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 24 publications
0
15
2
Order By: Relevance
“…A recent study (Khanal et al, 2018) also showed that precipitation plays a major role in the distribution of S. schistaceus in Nepal. Langurs in the Himalaya inhabit broad leaves subtropical forest at lower altitudes and temperate broadleaf forest at higher altitudes (Bishop, 1979; Curtin, 1982; Minhas et al, 2013; Sayers & Norconk, 2008; Sugiyama, 1976). Occasionally, these langurs are found in temperate coniferous forests above 4000m altitude (Bishop, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study (Khanal et al, 2018) also showed that precipitation plays a major role in the distribution of S. schistaceus in Nepal. Langurs in the Himalaya inhabit broad leaves subtropical forest at lower altitudes and temperate broadleaf forest at higher altitudes (Bishop, 1979; Curtin, 1982; Minhas et al, 2013; Sayers & Norconk, 2008; Sugiyama, 1976). Occasionally, these langurs are found in temperate coniferous forests above 4000m altitude (Bishop, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…As noted, folivorous primates are generally expected to traverse shorter distances in a given day than frugivores, but this can be altered when their foods are sufficiently scattered in space. Himalayan gray langurs on average travel over 1000 m per day at the three sites where this variable has been measured: Junbesi, Nepal (Curtin 1975), Langtang National Park, Nepal (Sayers and Norconk 2008), and Machiara National Park, Pakistan (Minhas et al 2012). Similar to some lowland gray langur populations (Newton 1992; Koenig et al 1997), these are comparable to the day ranges of some highly frugivorous primates (Di Fiore and Campbell 2007), including those with similar group sizes (Pombo et al 2004), and may include a greater degree of three-dimensional, altitudinal movement.…”
Section: Socioecological Models and Assumptions Reconsideredmentioning
confidence: 99%
“…For humans, this area is difficult to explore, so the biodiversity is likely very high; though for other reasons some threatened or endangered species inhabit this area. Threatened and endangered mammals living in this area includes the Rhesus macaque, the Himalayan brown bear, the Kashmir gray langur, the Indian wolf, the Indian leopard, the Snow leopard, the Markhor, the Kashmir red deer, the White-bellied musk deer and the Siberian ibex (Goldstein and Richard 1989;Woodford et al 2004;Bellemain et al 2007;Qamar et al 2008;Minhas et al 2010;Anwar et al 2011;Qureshi et al 2011;Kabir et al 2014;Raza et al 2015). In addition, birds such as the Western tragopan, the Peregrine falcon and the Cheer pheasant can be found (Raja et al 1999).…”
Section: Dear Editormentioning
confidence: 99%